Dismissal protection and long-term sickness absence: First evidence from Germany - Nicole Gürtzgen; Karolin Hiesinger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper analyses the causal effects of weaker dismissal protection on the incidence of long-term sickness (> six weeks). We exploit a German policy change, which shifted the threshold exempting small establishments from dismissal protection from five to ten workers. Using administrative data, we find a significantly negative reform effect on transitions into long-term sickness in the second year after a worker has entered an establishment. This response is due to a behavioural, rather than a compositional effect and is particularly pronounced among medium-skilled males. Our results further indicate that the reform did not alter the probability of involuntary unemployment after sickness.
Keywords: D02; I12; J28; J38; J88; J63; K31; 330; dismissal protection; long-term sickness; involuntary unemployment; difference-in-differences; administrative data; small establishments